Herpes simplex virus type 1 amplicon vectors for the infectious delivery and expression of genomic DNA loci. - Senior, S; Wade-Martins, R (2005)
A wide range of viral gene transfer technologies has been developed for gene therapy and functional genetic purposes. Different viral vectors vary in transgene capacity, range of infectivity and stability of expression. It is now becoming increasingly apparent that there are distinct advantages in using a complete genomic locus as a transgene to produce physiological levels of tissue-specific, sustained expression. However, the number of vector systems capable of delivering complete genomic loci is limited. The development of the infectious bacterial artificial chromosome system, a herpes simplex virus type 1-based vector that provides efficient infectious delivery and expression of bacterial artificial chromosome or P1-based artificial chromosome clone inserts, is reviewed. This system currently represents the leading technology capable of infectious delivery and expression of complete genomic DNA loci above 100 kb.